2017
DOI: 10.1590/s0100-736x2017000700008
|View full text |Cite
|
Sign up to set email alerts
|

Type C waterborne botulism outbreaks in buffaloes (Bubalus bubalis) in the Amazon region

Abstract: Botulism is a poisoning caused by botulinum neurotoxins (BoNTs). BoNTs serotypes C and D are involved in botulism outbreaks in cattle in several countries. Despite the high number of buffaloes worldwide, the real impact of botulism in buffaloes is not known, because it is not a notifiable disease in Brazil and only few studies have evaluated the occurrence of the disease in buffaloes. Those studies did not conduct diagnostic tests to confirm the presence of BoNTs. The objective of the present study was to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Most of the Brazilian animals (493,000, 37.4%) are located in the state of Pará [ 11 ], where they are reared within the Amazon biome and are very well adapted to the tropical climate and created mainly in extensive system [ 12 ]. This breeding system increases the exposure of these animals to health hazards and recently, our research group reported the occurrence of three outbreaks of botulism in buffaloes that affected two properties in the state of Pará [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the Brazilian animals (493,000, 37.4%) are located in the state of Pará [ 11 ], where they are reared within the Amazon biome and are very well adapted to the tropical climate and created mainly in extensive system [ 12 ]. This breeding system increases the exposure of these animals to health hazards and recently, our research group reported the occurrence of three outbreaks of botulism in buffaloes that affected two properties in the state of Pará [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are seven types of BoNTs (A–G) classified according to their antigenicity, although they all have similar mechanisms of action [ 1 , 2 , 3 ]. The BoNTs C and D are the main serotypes responsible for botulism in animals, including buffaloes [ 5 , 6 ]. Botulism is one of the leading causes of death in adult ruminants in Brazil due to the high mortality rates [ 7 ], even though botulism in buffaloes is poorly reported [ 5 , 6 , 8 ] and does not reflect the real economic impact of this disease in Brazilian herds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the most frequent diseases, rabies was ruled out by epidemiological data (as the disease only affects young buffalo calves) and by histopathological findings such as the absence of the Negri corpuscle in the CNS tissue and the presence of CNS gray matter necrosis, which is not correlated with rabies [28]. Likewise, botulism was also ruled out by epidemiology, as this intoxication is not common in suckling calves and the typical clinical signs (e.g., flaccid paralysis) were not observed in the studied buffaloes [29].…”
Section: Discussionmentioning
confidence: 97%